Photo luminescence: A probe for short, medium and long-range self-organization order in ZrTiO4 oxide - de Lucena, Poty R.; Leite, Edson Roberto; Pontes, Fenelon M.; Longo, Elson [UNESP]; Pizani, Paulo S.; Varela, José Arana [UNESP] (Elsevier B.V., 2006)
Photoluminescent disordered ZrTiO4 powders were obtained by the polymeric precursor soft-chemical method. This oxide system (ordered and disordered) was characterized by photoluminescence, Raman spectroscopy, X-ray diffraction, differential scanning calorimetry and UV vis absorption experiments. The UV absorption tail formation in the disordered oxides was related to the diminution of optical band gap. In the disordered phase, this oxide displayed broad band photoluminescence caused by change in coordination number of titanium and zirconium with oxygen atoms. The gap decreased from 3.09 eV in crystalline oxide to 2.16 eV in disordered oxide. The crystalline oxide presented an orthorhombic alpha-PbO2-type structure in which Zr4+ and Ti4+ were randomly distributed in octahedral coordination polyhedra with oxygen atoms. The amorphous-crystalline transition occurred at almost 700 degrees C, at which point the photoluminescence vanished. The Raman peak at close to 80-200 cm(-1) indicated the presence of locally ordered Ti-O-n and Zr-O-n polyhedra in disordered photoluminescent oxides. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: ZrTiO4; photo luminescence; polymeric precursor method; order-disorder level